The influence of normal distribution dispersion of fracture size on blockiness and REV of fractured rock masses - Ma, Tiantian; Xia, Lu (Frontiers in Earth Science, 2023)
The fractures of different sizes in rock masses influence the blockiness level of the rock. The distribution dispersion of fracture size is important for describing rock fragmentation. Based on a normal statistical distribution, the volume ratio of blocks to rock (B) and the representative elementary volume (REV) of the rock mass were obtained to describe the blockiness level. In addition, 4525 practical rock models were established to qualitatively reproduce the behavior of B with changing domain size. The results show that by comparing the degree of convergence, the REV of a rock mass is determined by the fracture size rather than the degree of fracture dispersion. The value of B increases with the distribution dispersion of fracture size, indicating a higher blockiness level. From the experimental analysis of coin tossing, when the number of trials exceeds 69, the random results are nearly stable. In this study, 100 calculations were performed. A formula to calculate the blockiness by considering the dispersion degrees of fracture size was obtained. Moreover, a positive linear correlation between B and the coefficient of variation of fracture size was obtained. The rate of increase in B has a parabolic relationship with the ratio of fracture size to fracture spacing (L)